Mobile technology supply factors and mobile money innovation: Thresholds for complementary policies - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2021)
This study complements the extant literature by assessing how enhancing supply factors of mobile technologies affect mobile money innovations for financial inclusion in developing countries. The mobile money innovation outcome variables are: mobile money accounts, the mobile phone used to send money and the mobile phone used to receive money. The mobile technology supply factors are: unique mobile subscription rate, mobile connectivity performance, mobile connectivity coverage and telecommunications (telecom) sector regulation. The empirical evidence is based on quadratic Tobit regressions and the following findings are established. There are Kuznets or inverted shaped nexuses between three of the four supply factors and mobile money innovations from which thresholds for complementary policies are provided as follows: (i) Unique adults' mobile subscription rates of 128.500%, 121.500% and 77.750% for mobile money accounts, the mobile used to send money and the mobile used to receive money, respectively; (ii) the average share of the population covered by 2G, 3G and 4G mobile data networks of 61.250% and 51.833% for the mobile used to send money and the mobile used to receive money, respectively; and (iii) a telecom sector regulation index of 0.409, 0.283 and 0.283 for mobile money accounts, the mobile phone used to send money and the mobile phone used to receive money, respectively. Some complementary policies are discussed, because at the attendant thresholds, the engaged supply factors of mobile money technologies become necessary, but not sufficient conditions of mobile money innovations for financial inclusion.
Keywords: D10; D14; D31; D60; O30; 330; Mobile money; technology diffusion; financial inclusion; inclusive innovation